The Influence of Ethnic‐Racial Identity Developmental Processes on Global Bicultural Competence Development. Issue 6 (20th July 2021) - Safa, M. Dalal; White, Rebecca M.B.; Knight, George P.
Abstract : This study investigated ethnic‐racial identity (ERI) developmental processes (i.e., exploration and resolution) as pathways for adolescents to develop global bicultural competence, or the ability to meet heritage and host cultural demands. The sample included 749 U.S. Mexican‐origin youth (30% Mexico‐born; 51% male) followed from early‐to‐late adolescence ( M age = 12.79–17.38 years). Longitudinal structural equation analyses revealed that youth's sequential engagement in ERI exploration and resolution (from early‐to‐middle adolescence) promoted global bicultural competence in late adolescence. The findings highlight the benefits of achieving clarity about one's ERI via self‐exploration efforts for adolescents' ability to respond effectively to bicultural demands. This study advances mechanisms via which ERI development may support youth adaptation to multiple cultural systems.